The English Students’ Problems in Facing TOEFL Test at STIE Madani Balikpapan During the Academic Year 2022/2023 - Muhammad Rochman (Journey: Journal of English Language and Pedagogy, 2023)
TOEFL is a language testing tool widely used in universities to check students’ capability in English mastery. The purpose of this study, titled "The English Students’ Problems in Facing the TOEFL Test at STIE Madani Balikpapan during the Academic Year 2022-2023," is to: (1) determine the issues experienced by Accounting Department students when performing the TOEFL test; and (2) determine ways to analyze among English students at STIE Madani Balikpapan with high TOEFL grades and low TOEFL grades. This study's sampling consists of 20 accounting students from the Economic Faculty at STIE Madani Balikpapan who took the TOEFL test. This study employed descriptive qualitative research. (1) Semi-structured interviews were used to gather information regarding the challenges that English students confront when completing the TOEFL test. (2) A closed-ended questionnaire was used to gather information about the ways in which students’ study, including study style, taking notes, ascertaining along the way, reading use, conning, and time direction. The consequences of this consultation bring out that, at that point, there are some issues that may arise while attempting the TOEFL test. The issues that have been identified are connected to a deficiency in English language achievement and cognition, inadequate time instruction, suffering absorption, and bearing issuing with the final retentions. The questionnaire consequences establish a few divergences in the field of study use between English language educators with eminent TOEFL grades and educators who have poor TOEFL grades